Saudi Arabia : Financial Sector Assessment Program Update-Detailed Assessment of Observance of the IOSCO Objectives and Principles of Securities Regulation. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses Saudi Arabia's Detailed Assessment of the Observance of the International Organization of Securities Commissions (IOSCO) objectives and principles of securities regulation. The Capital Market Authority (CMA) has made significant progress in establishing its supervision credentials, including issuing implementing regulations. The CMA has also entered into information sharing arrangements with other regulators in the region, and is a party to the IOSCO Multilateral Memorandum of Understanding Concerning Consultation, and Cooperation, and the Exchange of Information. The equity market in Saudi Arabia is of significant size, but has undergone significant change following the events of 2006 and the establishment of the CMA.